ANALISIS KOMPARASI UNTUNG-RUGI PPh FINAL UKM (PP 46 TAHUN 2013 ) VERSUS MENGGUNAKAN NORMA PERHITUNGAN - Irwan Irwan (Universitas Bunda Mulia, 2017)
Based on official data from the Ministry of cooperatives and SMEs (Small Medium enterprises) in Indonesia at this time, the number of SMES reached 56,5 million units. Almost 90% of the economy in Indonesia in contributed by SMES.As a means of taxation and Government doing extensification assignment tax regulated through Government Regulation (PP) No. 46 2013 to capture tax revenue from the sector SMEs and this rule makes it easier for SMES to conduct tax obligations. So in the SME sector pemajakan it is important to pay attention to how many release its gross per month from his business according to article 3 paragraph 2 PP No. 46 by 2013.The author would like to calculate (take into account) the extent to which tax savings that can be obtained by the taxpayers in this SME sector when applying the PP 46-year 2013. One way to compare with the use of different calculation of Norms.Based on the results of the study that the Taxpayers for Private Persons using the Net Income Calculation Norms, in general the imposition of final income tax of 1 percent of the circulation enterprises will benefit because reduced tax burden, the advantage is so large, it is also easy to do the calculation. In contrast to the private taxpayer groups user norm calculation under Rp 500,000,000, application of PPh final did not provide excess profits because of this group of calculation by using the norm became the main choice. Keyword : Comparisons of profit and loss, PPh Final SME (46 PP 2013), Norm Calculation